Recommendations for The Implementation Of Social Sanctions In Health Sector Corruption Cases - Budiarsih,; Achmad Taufan Efendi, (Technium Social Sciences Journal, 2024)
Law Number 20 of 2001 concerning Amendments to Law of the Republic of Indonesia Number 31 of 1999 concerning the Eradication of Corruption Crimes was made separately from the Criminal Code (Weetboek van Straftrecht) to make social sanctions an alternative to the imposition of other basic sanctions, but the technical implementation is still not yet clear. Based on this, researchers focus on recommendations for implementing social sanctions in cases of corruption in the health sector. The method used is normative juridical, namely through an approach and analysis of the relevant laws and regulations, the results of which can then be used as recommendations in the form of SOPs. The research results found that the Criminal Reform Policy Analysis in the New Criminal Code provides a better scope than the previous Criminal Code because the variety of contents in the new Criminal Code provides many choices of basic criminal sanctions. Recommendations for the application of social work punishment are part of the theory of legal objectives and a form of justice for victims, as well as criminal alternatives as supplements for perpetrators of criminal acts. Alternative social work criminal sanctions, which have just been included in the New Criminal Code through Law Number 1 of 2023, can be applied to corruption crimes in the health sector in the form of additional social criminal sanctions